2012
DOI: 10.1093/neuonc/nos195
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cycling hypoxia induces chemoresistance in glioblastoma multiforme by upregulating the expression and function of ABCB1

Abstract: Tumor cycling hypoxia is now a well-recognized phenomenon in animal and human solid tumors. However, how tumor cycling hypoxia impacts chemotherapy is unclear. In the present study, we explored the impact and the mechanism of cycling hypoxia on tumor microenvironment-mediated chemoresistance. Hoechst 33342 staining and hypoxia-inducible factor-1 (HIF-1) activation labeling together with immunofluorescence imaging and fluorescence-activated cell sorting were used to isolate hypoxic tumor subpopulations from hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 43 publications
1
74
1
1
Order By: Relevance
“…The underlying mechanisms of HIF-1α in suppression of apoptosis in laryngeal cancer cells induced by chemotherapeutic drugs remains to be further determined. Besides, it has already been confirmed that the enhancement of drug transport function is another important mechanism of MDR acquired by hypoxia in several kinds of tumor cells (Thews et al, 2011;Chou et al, 2012). The present study demonstrated that hypoxia carried out an increased function of transporting a variety of chemotherapeutic drugs such as 5-FU, cisplatin, adriamycin, paclitaxel and gemcitabine, leading to decreased intracellular drug concentration and reduced cytotoxicity.…”
Section: Discussionsupporting
confidence: 73%
“…The underlying mechanisms of HIF-1α in suppression of apoptosis in laryngeal cancer cells induced by chemotherapeutic drugs remains to be further determined. Besides, it has already been confirmed that the enhancement of drug transport function is another important mechanism of MDR acquired by hypoxia in several kinds of tumor cells (Thews et al, 2011;Chou et al, 2012). The present study demonstrated that hypoxia carried out an increased function of transporting a variety of chemotherapeutic drugs such as 5-FU, cisplatin, adriamycin, paclitaxel and gemcitabine, leading to decreased intracellular drug concentration and reduced cytotoxicity.…”
Section: Discussionsupporting
confidence: 73%
“…These studies indicate that miR-218 repression results in enhanced RTK activity in GBM, contributing to tumor cell survival under challenging microenvironmental conditions, including chemotherapeutic stress and severe hypoxia. Tumor hypoxia has been linked to chemoresistance, and recent studies demonstrate that low O 2 concentrations maintain tumor stem cells in an undifferentiated state (34,35). HIFs (and HIF2α in particular) promote GSC self-renewal, proliferation, and survival (36).…”
Section: Resultsmentioning
confidence: 99%
“…They also used cultured human colon carcinoma cells (HCT-116, HT-29, LoVo, and SW480), and observed that HIF-1α expression was significantly associated with MDR1/P-gp expression in human colon carcinoma cells as well [65]. In addition, the expression of the multidrug resistance-associated protein 1 (MRP1), another ABC transporter, is also induced by hypoxia, and have been reported in the majority of brain tumors, including glioblastomas [66].…”
Section: Hifs Induce Chemoresistance By Efflux Pump Expressionmentioning
confidence: 99%